ISLAMIC BANKING AND FINANCE second edition. - Ḥasan, Zubair ([S.l.] : ROUTLEDGE, 2023)
This book discusses the nature and theories which govern systems of Islamic finance including its most distinctive features and its relationship with conventional financial institutions. It explores the nature and role of money in modern economies and elaborates on the process of credit deposit creation, trade cycles and instruments for the creation of value in financial markets through the perspectives of Islamic finance. The author explains its characteristics, especially the rationale for the lack of interest-based financial activities. He examines the intrinsic ethical and humanistic frameworks that govern financial theories and practices and the models for the creation of value, risk-sharing and socially responsible investing, as well as the governance and regulation that these systems follow. The author also does a comparative assessment of conventional financial systems with Islamic finance with relevant examples, assesses the performance of Islamic systems and examines existing and expanding markets for Islamic finance. Lucid and cogent, this book is useful for scholars and researchers of Islamic finance, Islamic studies, economics, banking and finance in general.
Keywords: Banks and banking -- Religious aspects -- Islam; BUSINESS & ECONOMICS / Banks & Banking; SOCIAL SCIENCE / General